Pendekatan Teori Himpunan untuk Memahami Hubungan Antar Komunitas Adat di Papua - Nur Anisah; Nur Fadilah; Rinawati Tiflen; Rinawati Rumatoras; W. S. Yessi Gusman; Prihaten Maskhuliah (Lembag, 2025)
The set theory approach, which is often used in pure mathematics, can be applied to analyze relations between indigenous communities in Papua. This article maps cultural relations between three main indigenous communities Kamoro, Amungme, and Dani with a mathematical approach. Each community is represented as a collection of unique cultural elements, such as wood carving traditions (Kamoro), mountain beliefs (Amungme), and ancestral mummy traditions (Dani). This analysis involves the concepts of intersection, combination, and complementation to identify similarities, uniqueness, and potential conflicts and synergies between communities. This study found that although there is no direct cultural intersection, the combination of cultural elements shows significant richness. This approach provides a systematic tool for understanding relationships between communities, supporting cultural preservation, and creating social harmony.